Arguments - Forrest, Jessica ([?], 2017)
This guide will provide you with a strong insight into this rare skill. Whilst by no means an exhaustive resource, by having read this guide you should understand everything you need to know to be comfortable arguing with anyone from a lover to an angry colleague. On your journey through this eBook you will have dipped and dived through formal logic and academic arguments, learning how to present and consider your ideas analytically along the way. You will have also jumped into the world of confrontational arguments, discovering how to defuse, calm and communicate in your conflict with those you know. Further down the path, you will take a crash course in body language and non-verbal communication, gaining the ability to alter and recognize the hidden signals people display. Finally, you will also learn how to appreciate the differences in approach when dealing with conflicts between colleagues, friends, family members and strangers.